High Cytoplasmic CXCR4 Expression Predicts Prolonged Survival in Triple-Negative Breast Cancer Patients Treated with Adjuvant Chemotherapy - Bobae Shim; Min-Sun Jin; Ji Hye Moon; In Ae Park; Han Suk Ryu (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background Chemokine receptor CXC chemokine receptor type 4 (CXCR4) and its ligand CXC motif chemokine 12 (CXCL12; stromal cell-derived factor-1) are implicated in tumor growth, metastasis, and tumor cell-microenvironment interaction. A number of studies have reported that increased CXCR4 expression is associated with worse prognosis in triple-negative breast cancer (TNBC), but its prognostic significance has not been studied in TNBC patients treated with adjuvant chemotherapy. Methods Two hundred eighty-three TNBC patients who received adjuvant chemotherapy were retrospectively analyzed. Tissue microarray was constructed from formalin-fixed, paraffin-embedded tumor tissue and immunohistochemistry for CXCR4 and CXCL12 was performed. Expression of each marker was compared with clinicopathologic characteristics and outcome. Results High cytoplasmic CXCR4 expression was associated with younger age (p = .008), higher histologic grade (p = .007) and lower pathologic stage (p = .045), while high CXCL12 expression was related to larger tumor size (p = .045), positive lymph node metastasis (p = .005), and higher pathologic stage (p = .017). The patients with high cytoplasmic CXCR4 experienced lower distant recurrence (p = .006) and better recurrence-free survival (RFS) (log-rank p = .020) after adjuvant chemotherapy. Cytoplasmic CXCR4 expression remained an independent factor of distant recurrence (p = .019) and RFS (p = .038) after multivariate analysis. Conclusions High cytoplasmic CXCR4 expression was associated with lower distant recurrence and better RFS in TNBC patients treated with adjuvant chemotherapy. This is the first study to correlate high CXCR4 expression to better TNBC prognosis, and the underlying mechanism needs to be elucidated in further studies.